A DYNAMIC LOCATION ESTIMATION TECHNIQUE BASED ON FINGERPRINT USING A REDUCED RADIO MAP IN WIRELESS SENSOR NETWORKS - Tatar, Yetkin; Yildirim, Gungor (Gazi Univ, Fac Engineering Architecture, 2014)
In closed areas, fingerprint location estimation algorithms using a radio map, which can be used in wireless sensor networks, consist of two phases, mapping and location estimation. There are several important criterions in the phases, for example using of a radio map which has a small capacity and which shows a comprehensive RSSI dispersion, a quick position calculation, a good accuracy rate, and so on. In the study, a novel technique which employs K-Means method to decrease size of the radio map by reducing separately RSSI (Received Signal Strength Indicator) data of the anchors has been proposed for indoor position detection in WSNs. Besides, a subfield construction process to increase the accuracy of the estimation has been carried out. In the location estimation phase, a technique which is different from K-Nearest Neighbour (KNN) has been preferred. In this technique, unlike KNN the number of the decision cells varies dynamically according to RSSI data received. The system was implemented in a closed environment by using TELOSB nodes. The results of the experiments and the calculations were compared with the results of well-known deterministic methods based on KNN and the validation of the proposed system was tested.
Keywords: Localization; Wireless Sensor Networks; Fingerprint